Heat Shock Protein A6 Is Especially Involved in Enterovirus 71 Infection - Jia, Jiaoyan; Liu, Ge; Zhong, Jianfeng; Yan, Ran; Song, Xun; Zheng, Kai; Ren, Zhe; He, Zhendan; Zhu, Qinchang (Frontiers in Microbiology, 2022)
Hand foot and mouth disease (HFMD) caused by Enterovirus 71 (EV71) infection is still a major infectious disease threatening children's life and health in the absence of effective antiviral drugs due to its high prevalence and neurovirulence. A study of EV71-specific host response might shed some light on the reason behind its unique epidemiologic features and help to find means to conquer EV71 infection. We reported that host heat shock protein A6 (HSPA6) was induced by EV71 infection and involved infection in both Rhabdomyosarcoma (RD) cells and neurogliocytes. Most importantly, we found that EV71 did not induce the expression of other heat shock proteins HSPA1, HSPA8, and HSPB1 under the same conditions, and other HFMD-associated viruses including CVA16, CVA6, CVA10, and CVB1-3 did not induce the upregulation of HSPA6. In addition, EV71 infection enhanced the cytoplasmic aggregation of HSPA6 and its colocalization with viral capsid protein VP1. These findings suggest that HSPA6 is a potential EV71-specific host factor worthy of further study.